Are Bank Lending Shocks Important for Economic Fluctuations? - Jørn Inge Halvorsen; Dag Henning Jacobsen (Norges Bank, 2009)
We analyze the importance of bank lending shocks on real activity in Norway and the UK, using structural VARs and based on quarterly data for the past 21 years. The VARs are identified using a combination of sign and short-term zero restrictions, allowing for simultaneous interaction between various variables. We find that a negative bank lending shock causes output to contract. The significance of bank lending shocks seems evident as they explain a substantial share of output gap variability. This suggests that the banking sector is an important source of shocks. The empirical analysis comprises the Norwegian banking crisis (1988-1993) and the recent period of banking failures and recession in the UK. The results are clearly non-negligible also when omitting periods of systemic banking distress from the sample.
hdl:11250/2497613
Keywords: 330; VAR; identification; monetary policy; bank lending